2015
DOI: 10.1089/scd.2014.0323
|View full text |Cite
|
Sign up to set email alerts
|

Rbm46 Regulates Trophectoderm Differentiation by StabilizingCdx2mRNA in Early Mouse Embryos

Abstract: Blastocyst formation represents the first lineage specification by segregation of the trophectoderm from the inner cell mass in early embryonic development. Transcriptional regulation of Cdx2, which is selectively expressed in and essential for the specification of trophectoderm, has been extensively studied. However, post-transcriptional regulation of Cdx2 remains largely unknown. In this study, we report that RNA-binding protein motif 46 (Rbm46), an RNA-binding motif protein with unknown function, directly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…As many of these proteins (70%) are still unknown to bind RNA, we also cannot exclude the presence of contaminant proteins that were non-specifically copurified with RBPs. Among the hESC-specific RBPs, we identified RBM46, which has been shown to bind the Cdx2 mRNA in mouse embryos (Wang et al, 2015) and whose precise levels are key determinants in controlling mESC differentiation (Zhai et al, 2017). This observation is consistent with the notion that some hESC-specific RBPs could represent general stem cell-related factors, irrespective of the species of origin.…”
Section: Resultssupporting
confidence: 85%
“…As many of these proteins (70%) are still unknown to bind RNA, we also cannot exclude the presence of contaminant proteins that were non-specifically copurified with RBPs. Among the hESC-specific RBPs, we identified RBM46, which has been shown to bind the Cdx2 mRNA in mouse embryos (Wang et al, 2015) and whose precise levels are key determinants in controlling mESC differentiation (Zhai et al, 2017). This observation is consistent with the notion that some hESC-specific RBPs could represent general stem cell-related factors, irrespective of the species of origin.…”
Section: Resultssupporting
confidence: 85%
“…For example, a recent study reported alterations in six metastable epialleles (CpG sequences with high inter-individual variation presumably due to stochastic methylation in early development) in 84 infants conceived during the protein-energy- and methyl-donor limited Gambian rainy season, in comparison to infants born in the dry season(57). Strikingly, one of the six nutrition-dependent epilalleles in the Gambian cohort(57), RBM46, encoding a regulator of early blastocyst and trophoectoderm differentiation(58), completely matched one of the G1 DMRs in our study (Gambia DMR hg18 , chr4:155,922,422-155,922,489, Barbados DMR: hg18, chr4: 155,921,670-155,922,589). Furthermore, DNA methylomics on 24 infants exposed to the war-related 1944/45 Dutch hunger winter at the time of conception, in comparison to their unaffected siblings, identified 181 DMRs, many of which related to growth and metabolism(59).…”
Section: Discussionsupporting
confidence: 53%
“…ESCs were grown on glass coverslips (Fisher Scientific) and stained as previously described ( Wang et al., 2015 ).…”
Section: Methodsmentioning
confidence: 99%